Streptococcus pneumoniae Impairs Maturation of Human Dendritic Cells and Consequent Activation of CD4+ T Cells via Pneumolysin - Antje D. Paulikat; Lea A. Tölken; Lana H. Jachmann; Gerhard Burchhardt; Sven Hammerschmidt; Nikolai Siemens (Journal of Innate Immunity, 2022)
Influenza A Virus (IAV), Staphylococcus aureus (staphylococci), and Streptococcus pneumoniae (pneumococci) are leading viral and bacterial causes of pneumonia. Dendritic cells (DCs) are present in the lower respiratory tract. They are characterized by low expression of co-stimulatory molecules, including CD80 and CD86 and high capacity of antigen uptake. Subsequently, DCs upregulate co-stimulatory signals and cytokine secretion to effectively induce T-cell priming. Here, we investigated these processes in response to bacterial and viral single as well as coinfections using human monocyte-derived (mo)DCs. Irrespective of single or coinfections, moDCs matured in response to IAV and/or staphylococcal infections, secreted a wide range of cytokines, and activated CD4+, CD8+ as well as double-negative T cells. In contrast, pneumococcal single and coinfections impaired moDC maturation, which was characterized by low expression of CD80 and CD86, downregulated expression of CD40, and a mild cytokine release resulting in abrogated CD4+ T-cell activation. These actions were attributed to the cholesterol-dependent cytotoxin pneumolysin (Ply). Infections with a ply-deficient mutant resulted in restored moDC maturation and exclusive CD4+ T-cell activation. These findings show that Ply has important immunomodulatory functions, supporting further investigations in specific modalities of Ply-DC interplay.